Five Fatty Acyl-Coenzyme A Reductases Are Involved in the Biosynthesis of Primary Alcohols in Aegilops tauschii Leaves - Wang, Meiling; Wu, Hongqi; Xu, Jing; Li, Chunlian; Wang, Yong; Wang, Zhonghua (Frontiers in Plant Science, 2017)
The diploid Aegilops tauschii (Ae. tauschii) is the D-genome donor to hexaploid wheat (Triticum aestivum) and represents a potential source for genetic study in common wheat. The ubiquitous wax covering the aerial parts of plants plays an important role in protecting plants against nonstomatal water loss. Cuticular waxes are complex mixtures of very long-chain fatty acids, alkanes, primary and/or secondary alcohols, aldehydes, ketones, esters, triterpenes, sterols, and flavonoids. In the present work, primary alcohols were identified as the major components of leaf cuticular wax in Ae. tauschii, with C26:0-OH being the dominant primary alcohol. Analysis by scanning electron microscope (SEM) revealed that dense platelet-shaped wax crystals were deposited on leaf surfaces of Ae. tauschii. Ten putative wax biosynthetic genes encoding fatty acyl-coenzyme A reductase (FAR) were identified in the genome of Ae. tauschii. Five of these genes, Ae.tFAR1, Ae.tFAR2, Ae.tFAR3, Ae.tFAR4 and Ae.tFAR6, were found expressed in the leaf blades. Heterologous expression of the five Ae.tFARs in yeast (Saccharomyces cerevisiae) showed that Ae.tFAR1, Ae.tFAR2, Ae.tFAR3, Ae.tFAR4 and Ae.tFAR6 were predominantly responsible for the accumulation of C16:0, C18:0, C26:0, C24:0 and C28:0 primary alcohols, respectively. In addition, nine Ae.tFAR paralogous genes were located on D chromosome of wheat and the wheat nullisomic–tetrasomic lines with the loss of Ae.tFAR3 and Ae.tFAR4 paralogous genes had significantly reduced levels of primary alcohols in the leaf blades. Collectively, these data suggest that Ae.tFAR1, Ae.tFAR2, Ae.tFAR3, Ae.tFAR4 and Ae.tFAR6 encode alcohol-forming FARs involved in the biosynthesis of primary alcohols in the leaf blades of Ae. tauschii. The information obtained in Ae. tauschii enables us to better understand wax biosynthesis in common wheat.